Use of humanised reporter cell lines for high-throughput detection of allergic sensitization - Kalli, Marina (2021)
The prevalence of allergic diseases is growing rapidly in Europe. Today, it is estimated that more than 150 million individuals living in EU suffer from chronic allergic diseases, half of whom are underdiagnosed or poorly managed due to lack of awareness and shortage of medical specialists. Moreover, many patients do not report their symptoms or are not correctly diagnosed, while approximately 45% of the patients have never received an allergy diagnosis.